Macro and micro-morphological characteristics of Plantago seeds and its implication for species identification - Verma, Ashutosh kUMAR; Kumar Avinash Bharti, Neelam Gautam (Current Botany, 2017)
Seed morphology of five species of Plantago (P. psyllium, P.ovata, P. lanceolata, P. major and P. arenaria) was examined under scanning electron microscope. Macro- and micro-morphological characters, including seed shape, colour, size, shape of cavity, surface ornamentation and epidermal cell shape are presented.Â Marked difference among the species noted with respect of considered traits and a key for the identification of the investigated taxa based on seed characters is provided.Â Â